2022
DOI: 10.1111/bph.15937
|View full text |Cite
|
Sign up to set email alerts
|

KS0365, a novel activator of the transient receptor potential vanilloid 3 (TRPV3) channel, accelerates keratinocyte migration

Abstract: Background and Purpose: Ca 2+ signalling mediated by the thermosensitive, nonselective, Ca 2+ -permeable transient receptor potential channel TRPV3 is assumed to play a critical role in regulating several aspects of skin functions, such as keratinocyte proliferation, differentiation, skin barrier formation and wound healing. Studying the function of TRPV3 in skin homeostasis, however, is still constrained by a lack of potent and selective pharmacological modulators of TRPV3.Experimental Approach: By screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Other data indicated that TRPV3 regulates nitric oxide synthesis in the skin, thus promoting wound healing in vivo [153]. A synthetic activator KS0365 accelerated keratinocyte migration that paralleled strong TRPV3-mediated calcium responses in migrating front cells and in leading edges, which suggests the role of TRPV3 in re-epithelialization upon skin wounding [54].…”
Section: Wound Healing and Barrier Functionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other data indicated that TRPV3 regulates nitric oxide synthesis in the skin, thus promoting wound healing in vivo [153]. A synthetic activator KS0365 accelerated keratinocyte migration that paralleled strong TRPV3-mediated calcium responses in migrating front cells and in leading edges, which suggests the role of TRPV3 in re-epithelialization upon skin wounding [54].…”
Section: Wound Healing and Barrier Functionsmentioning
confidence: 96%
“…A novel synthetic activator of TRPV3, KS0365 showed a higher efficacy and potency than 2-APB. The compound also acted non-selectively, acting on TRPV1 and TRPV2 channels and triggering intracellular calcium release at higher concentrations [54].…”
Section: Synthetic Agonistsmentioning
confidence: 99%
“…TRPV3, on the other hand, can induce fibrosis through TRPV3/TSLP/Smad2/3 pathway, resulting in significantly increased expression levels of α-SMA, fibronectin, COL1A1, and TSLP ( 62 ). Additionally, the selective TRPV3 activator KS0365 has been shown to accelerate the migration of KCs and promote re-epithelialization during physiological wound healing ( 63 ). Furthermore, the presence of TRPV3 in macrophage lysosomes may play a crucial role in the inflammatory phase of PS ( 64 ).…”
Section: Cutaneous Wound Healing and The Mechanism Of Psmentioning
confidence: 99%
“…Studies have shown that the new TRPV3 channel activator KS0365 promotes wound healing by accelerating the re-epithelialization of KCs, while the broad-spectrum channel blocker ruthenium red and siRNA-mediated TRPV3 knockdown inhibit this process ( 63 , 159 ). This finding indicates that overexpression of TRPV3 channels can promote excessive wound healing leading to the formation of PS.…”
Section: Modulation Of Trp Channels In Psmentioning
confidence: 99%
“…For example, TRPV3 is a promising target for improving wound healing. In the epidermis, appropriately-activated TRPV3 can promote keratinocyte proliferation, differentiation, and migration and inhibit cell apoptosis, thus accelerating re-epithelialization [ 76 , 94 ]. In the dermis, TRPV3 is involved in the process of dermal extracellular matrix deposition, which can improve the integrity of injured skin, which also suggests the potential of TRPV3 in regulating scar formation [ 95 ].…”
Section: Potential Target For Skin Regenerationmentioning
confidence: 99%